Management of Colorado potato beetle in invasive frontier areas - Cong WANG; Han XU; Xu-bin PAN (Journal of Integrative Agriculture, 2020)
Colorado potato beetle (CPB) is one of the most devastating invasive insects and it is native to North America. It feeds on several wild species of the genus Solamum, such as S. elaeagnifolium and S. rostratum Dunal, and is one of the major pests of potato and eggplant. Beginning in the early 19th century, CPB has rapidly spread across North America, Europe, and Central Asia. CPB was first reported to invade Xinjiang of China in 1993 and it was effectively controlled in Mori County. Since 2013, CPB has also been found in Jilin and Heilongjiang in Northeast China, and it likely migrated to these provinces from Russia. Thus, China has become the frontier for the global CPB spread, and risk management and monitoring systems for this pest are urgently needed. Here, we summarize pest management methods that are used in areas at the frontier of the CPB invasion, and put forward frameworks for further preventing and controlling of the spread of CPB. The management methods for CPB can also serve as an example for the control of invasive species mitigation in frontier areas.